Digital Governance in Human Resources Development (HRD) Portal with Soft Systems Methodology Approach, Study of BUMN Holding Survey Services - Arif Bijaksana Satria Negara; Rachma Fitriati (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
The rapid development of technology has significantly impacted various aspects of human life, including in the world of work and the development of human resources (HR). Digital governance is the development of the concept of E-Government, which focuses more on user participation in its application. Implementing digital governance is a human capital application transforming how companies manage their human resources. For more than three decades, SBU Marine Services used a time-based payroll system. However, since 2021, the company switched to a competency-based approach. This change has led to an income gap between long-standing contract employees and new joiners. In addition, the salary data collection system still uses spreadsheets, which have several potential governance issues, such as transparency of the payroll system, information on employee training and grading data, etc. This study uses the soft systems methodology (SSM) approach to analyze digital governance using the HRD Portal application in SBU Marine Services. The results showed no policy governing contract employee governance in SBU Marine Services, so the HRD Portal is needed. This research recommends creating an HRD Portal SOP policy to measure and monitor employee performance more effectively and efficiently. The contribution of this study, with the HRD Portal SOP policy, can change the payroll system from a time-based system to a competency-based system, overcome the social gap in contract employee income, and increase transparency and fairness in human capital management at SBU Marine Services.